DETERMINING FACTORS OF CONTINUANCE INTENTION TO USE QR CODE MOBILE PAYMENT AMONG URBAN MILLENNIALS IN INDONESIA: Empirical Study on DANA Mobile Payment - Shella Azizah; Bambang Purwoko Kusumo Bintoro (Sean Institute, 2023)
This research was conducted in order to determine the parameters of Continuance Intention to Use QR Code Mobile Payment DANA in Urban Millennial population in Indonesia. Using the basis of the DeLone & Mc Lean Information System Success Model, the type of data used is primary data obtained from the questionnaires. The questionnaire were distributed to QR Code Mobile Payment DANA users who were born between 1981 and 2000 and domiciled in the Jakarta Metropolitan area (Jakarta, Bogor, Depok, Tangerang, Bekasi). The method used in sampling is purposive sampling. Obtained data sample of 111 respondents comprised of 66.7% women and 33.3% men. The data was processed using SEM-PLS through the SmartPLS 3 software. The results showed that (1) Trust has a significant effect on Continuance Intention, (2) Flow has a significant effect on Continuance Intention, (3) User Satisfaction has a significant effect on Continuance Intention, (4) has a significant effect on Flow, (5) Flow has a significant effect on User Satisfaction, (6) System Quality has a significant effect on Trust, (7) System Quality has no effect on Flow, (8) System Quality has no effect on User Satisfaction, (9) Information Quality has no effect on Trust (10) Information Quality has no effect on Flow, (11) Information Quality has a significant effect on User Satisfaction, (12) Service Quality has a significant effect on Trust, (13) Service Quality has a significant effect on Flow, (14) Service Quality has no effect on User Satisfaction.